Oxford handbook of nucleic acid structure - Neidle, Stephen (Oxford University Press, 1999)
The Oxford Handbook of Nucleic Acid Structure is a comprehensive reference on all aspects of nucleic acid structure, with particular emphasis on the results from X-ray crystallography and NMR studies. In nineteen chapters by leading experts, it describes in detail the variety of DNA and RNA structural types discovered to date, progressing systematically through the polymorphs of double helical DNA through to the higher-order organizations of triplexes, quadruplexes, and junctions, then to RNA structures in their various degrees of complexity